Strengthening regional preparedness and surge workforce through the Global Outbreak Alert and Response Network - Salmon, Sharon (Western Pacific Surveillance and Response, 2025)
This editorial introduces the Special Edition on the Global Outbreak Alert and Response Network (GOARN) published by Western Pacific Surveillance and Response. The articles in this Special Edition reflect on insights from expert deployments through GOARN and the experiences of GOARN partner institutions across the Western Pacific Region since the network's formation in 2000. The Special Edition also serves as a call for continued strengthening of and investment in the people, systems and partnerships that facilitate effective emergency response.
Keywords: GOARN; Global Outbreak Alert and Response Network; public health emergencies; capacity building; emergency preparedness; health workforce